Cardiovascular effects and mechanisms of sodium-glucose cotransporter-2 inhibitors - Fan Yang (KeAi Communications Co., Ltd., 2020)
Sodium-glucose cotransporter-2 inhibitors (SGLT2 inhibitors) are a new type of drug for the treatment of diabetes, and they have been proven to have a good hypoglycemic effect. Several lines of clinical evidence have shown that SGLT2 inhibitors can significantly reduce the risks of atherosclerosis, hospitalization for heart failure, cardiovascular death, and all-cause mortality and delay the progression of chronic kidney disease. Because of the protective effects of SGLT2 inhibitors on the heart and kidney, they are being studied for the treatment of heart failure and chronic kidney disease in patients without diabetes. Therefore, it is necessary for cardiologists, patients with diabetes, and nephrologists to fully understand this type of drug. In this review, we summarize the following three aspects of SGLT2 inhibitors: the recent clinical evidence of their cardiovascular benefits, their mechanisms of action, and their safety.